El derecho a la democracia en las Américas - Muñoz, Heraldo (Estudios Internacionales, 1995)
In the inter-American system, there has historically been a tendency to understand democracy as a legal obligation. Considering that the "right to democracy" has become a normative imperative and is being implemented through peaceful collective action, in this paper it is proposed that the Organization of American States has to fulfill the role of seeking a convergence between doctrine and concrete action. First, it explains how the doctrine and practice of democracy have evolved in the inter-American system, pointing out the main milestones in this regard. Then, reference is made to some recent initiatives of the organization with respect to democracy, the cases of Haiti, Peru and Guatemala, as well as the supervision of elections in several countries and the revision of the traditional concept of sovereignty.